Study on the Alkaloids in Tibetan Medicine Aconitum pendulum Busch by HPLC–MS(n) Combined with Column Chromatography - Wang, Beibei (J Chromatogr Sci, 2016)
A rapid, convenient and effective identification method of alkaloids was established and an attempt on isolating and analyzing the alkaloids in Aconitum pendulum Busch was conducted successfully. In this article, four high-content components including deoxyaconitine, benzoylaconine, aconine and neoline were isolated by using column chromatography. HPLC–MS(n) was employed to deduce the regulations of fragmentation of diterpenoid alkaloids which displayed a characteristic behavior of loss of CO(28u), CH(3)COOH(60u), CH(3)OH(32u), H(2)O(18u) and C(6)H(5)COOH(122u). Then, according to fragmentation regulation of mass spectrometry, 42 alkaloids were found in A. pendulum. Among them, 38 compounds were identified and 29 alkaloids were reported for the first time for this herb. Therefore, this means that HPLC–MS(n) combined with column chromatography could work as an effective and reliable tool for rapid identification of the chemical components of herbal medicine.